Characterising the Gulf of Mexico Yield Surface at High Stress - Eagle, Liam. (Tufts University. Tisch Library., 2021)
Thesis (M.S.)--Tufts University, 2021.; Submitted to the Dept. of Civil Engineering.; Advisor: John Germaine.; Committee: Richard Plumb, and Luis Dorfmann.; Keyword: Engineering.